CATESTATIN AS A NOVEL MARKER OF CARDIOVASCULAR RISK IN SYSTEMIC HYPERTENSION - E. Yu. Gubareva (Российский кардиологический журнал, 2018)
Review of the key studies on antihypertensive, vasodilatatory, angiogenic and antiapoptotic action of catestatin — a peptide resulting from endogenic protease interaction with chromogranin А. Plasma levels of catestatin correlate negatively with the hypertension phenotype. Pathogenetic role is discussed for catestatin in development of essential hypertension and its possible influence as a marker of cardiovascular risk stratification.